Low-drying-shrinkage alkali slag seawater sea sand concrete and preparation method thereof
By preparing low drying shrinkage alkali slag concrete through a mechanochemical process with seawater and sea sand, the method addresses structural cracking and ecological damage, achieving performance comparable to traditional cement while conserving resources.
Patent Information
- Application Number
- CN202411416615.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-11
AI Technical Summary
Traditional cement materials exhibit high drying shrinkage, leading to cracks in building structures and increased risk of corrosion, limiting their wide application, while the excessive exploitation of river sand for concrete production causes ecological damage.
A method involving ball-milling slag and an activator to create a single-component alkali slag cement, mixed with seawater and sea sand, optimizing the mix ratio and stirring process to prepare low drying shrinkage alkali slag seawater sea sand concrete.
The method reduces drying shrinkage to levels comparable to ordinary Portland cement, enhancing mechanical properties and addressing ecological issues by utilizing abundant sea sand and seawater resources, thus promoting sustainable construction.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and particularly relates to low drying shrinkage alkali slag seawater and sea sand concrete and a preparation method thereof. Background Art
[0002] About 70% of the earth's surface is covered by water, of which freshwater resources account for only 3.5%, while seawater accounts for 96.5%. In order to meet the needs of concrete production, the excessive exploitation of river sand has caused serious ecological problems in my country, leading to the destruction of the riverbank ecological environment and the damage to the foundations of inland river bridges. Compared with river sand, sea sand resources are abundant, and my country has vast sea areas and long coastlines. Sea sand has gradually received attention as an alternative resource. Sea sand has the advantages of large reserves, low mining difficulty, local materials, and low transportation costs. Therefore, studying the application of sea sand and seawater instead of river sand and fresh water in concrete production not only has significant ecological benefits, but also has obvious economic value.
[0003] As a new type of green building cementitious material, alkali-activated cementitious materials are increasingly attracting the attention of scientific researchers. Compared with ordinary Portland cement, the carbon dioxide emissions and energy consumption of alkali-activated cementitious materials produced by producing the same unit mass are only 20% and 40% of ordinary Portland cement. By using seawater and sea sand to prepare alkali-activated slag concrete, it can not only effectively alleviate the shortage of fresh water and river sand resources, but also play a positive role in protecting the environment and reducing environmental pressure, which can be said to kill two birds with one stone.
[0004] The high drying shrinkage of traditional cement often causes cracks in building structures, which in turn increases the risk of invasion of corrosive substances and the possibility of steel corrosion. In addition, the large drying shrinkage of the alkali-slag system itself also limits its wide application. Therefore, the development of an alkali-slag concrete with low drying shrinkage is of great significance for promoting the application of this material in the construction field. Summary of the invention
[0005] The present invention is achieved through the following technical solutions: A method for preparing low drying shrinkage alkali slag seawater sea sand concrete comprises the following steps: firstly, ball-milling slag and an activator by mechanical chemical force to obtain a powder, namely, single-component alkali slag cement, wherein the slag is S95-grade granulated blast furnace slag, and the activator is anhydrous sodium silicate with an alkali modulus of 1.4, wherein the mass of Na2O in the anhydrous sodium silicate accounts for 4% of the mass of the slag and the anhydrous sodium silicate; and then, the single-component alkali slag cement is mixed with sea sand and seawater to prepare alkali slag seawater sea sand concrete.
[0006] Furthermore, the sea sand has, by mass percentage, a water content of ≤6.0%, a mud content of ≤3.0%, a chloride ion content of ≤0.02%, and a shell content of ≤5.0%.
[0007] Furthermore, the seawater is prepared according to a concentration ratio of NaCl:MgCl2:Na2SO4:CaCl2:KCl:NaHCO3=24.53:5.2:4.09:1.16:0.695:0.201.
[0008] Furthermore, the particle size of the sea sand is less than 5 mm, and the fineness modulus is 2.71, which is medium sand in Zone II.
[0009] Furthermore, a method for preparing low drying shrinkage alkali slag seawater sea sand concrete comprises the following steps: (1) After drying and cooling, the slag is mixed with anhydrous sodium silicate with an alkali modulus of 1.4 and ball milled for 1 h at a speed of 75 r / min and a ball-to-material ratio of 7.5:1. After ball milling, the powder obtained is screened to obtain a single-component alkali slag cement; (2) Weigh seawater, sea sand and single-component alkali-slag cement according to the proportion, and mix them with a mortar mixer to obtain seawater-sand-alkali-slag concrete.
[0010] Furthermore, the mass ratio of seawater to single-component alkali-slag cement is 0.43:1; the mass ratio of single-component alkali-slag cement to sea sand is 1:2.
[0011] Furthermore, the stirring process is as follows: after adding seawater to the single-component alkali slag cement, stirring at a low speed for 30 seconds, then adding sea sand within 30 seconds, stirring at a high speed for 30 seconds, pausing for 90 seconds to mix the materials, and then continuing to stir at a high speed for 60 seconds.
[0012] The present invention provides an optimal mix ratio of a single-component alkali-slag concrete, and the beneficial effects of the present invention are: (1) The present invention uses seawater and sea sand as raw materials for engineering construction, which can save material transportation costs and have good economic effects. On the other hand, it can save river sand resources and fresh water resources, promote engineering construction, and have good social benefits.
[0013] (2) The present invention uses seawater and sea sand instead of deionized river sand as raw materials to prepare alkali slag concrete. The chloride ions in seawater and CaCO3, the main component of shells in sea sand, are conducive to reducing the drying shrinkage of alkali slag mortar. Its drying shrinkage performance is close to that of ordinary Portland cement, which effectively improves the problems of large drying shrinkage and easy cracking of alkali slag concrete. In addition, since seawater increases the pH value of concrete, and the pH value is very important for the polymerization reaction of alkali-induced materials, it can promote the alkali slag material to generate more CSH gel, so the seawater and sea sand alkali slag concrete obtained by this ratio also has good mechanical properties.
[0014] (3) The present invention uses industrial waste slag as raw materials to prepare alkali slag concrete. The alkali slag seawater sea sand concrete prepared by mechanochemical method has the advantages of high efficiency and energy saving, and the mechanochemical method can induce physical and chemical changes in alkali-activated cementitious materials, thereby improving the drying shrinkage performance of single-component alkali-activated cementitious materials. DETAILED DESCRIPTION
[0015] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.
[0016] The experimental materials and properties involved in the following embodiments are as follows: (1) The slag is S95 grade granulated blast furnace slag from Yanxing Mineral Products Processing Plant in Lingshou County, Hebei Province. The basic physical quantities of the slag are shown in Table 1. The slag samples were subjected to XRF analysis, and the chemical composition analysis results are shown in Table 2.
[0017] (2) In the embodiments, three types of sand, namely sea sand, desalinated sea sand and river sand, are used as aggregates. Sea sand and desalinated sea sand are both from Zhangpu County, Zhangzhou City, Fujian Province. Desalinated sea sand is obtained by washing and drying sea sand. River sand comes from Jinjing Town, Jinjiang City, Quanzhou City, Fujian Province, and all are undried river sand. Among them, the moisture content, mud content, chloride ion content and shell content are determined according to GB / T14684-2022 "Construction Sand". After measurement, the specific information of the three types of sand is shown in Table 3. The moisture content, sand content, chloride ion content and shell content of the three types of sand all meet the requirements of the specification.
[0018] (3) The grading of sea sand, desalinated sea sand and river sand was measured according to the Standard Method for Quality and Inspection of Sand and Stone for Ordinary Concrete (JCJ52-2006), and the cumulative sieve residue is shown in Table 4. Among them, A1, A2, A3, A4, A5 and A6 are the cumulative sieve residue percentages of 4.75mm, 2.35mm, 1.18mm, 500μm, 300μm and 150μm sieves respectively. The fineness modulus of sand is calculated according to Formula 1-1. After calculation, the fineness modulus of sea sand is 2.71, which is medium sand in Zone II; the fineness modulus of desalinated sea sand is 1.86, which is fine sand in Zone III; the fineness modulus of river sand is 3.03, which is medium sand in Zone II. Before use, screen out particles with a particle size of 5mm or more from river sand.
[0019] (4) Sodium chloride (NaCl), magnesium chloride (MgCl2), sodium sulfate (Na2SO4), calcium chloride (CaCl2), potassium chloride (KCl), and sodium bicarbonate (NaHCO3) are used. The present invention mainly focuses on the influence of chloride ions and pH value in seawater on the performance of concrete. Therefore, only substances containing chloride ions (NaCl, MgCl2, etc.) and substances affecting pH (Na2SO 4、NaHCO3), artificial seawater was prepared according to the specification ASTM D1141-89, and the proportion of the preparation is shown in Table 5. The water used in all experiments was deionized water, and the seawater referred to in the embodiments was the artificial seawater.
[0020] Among them, NaCl (granular) comes from Tianjin Zhiyuan Co., Ltd., and the NaCl content is not less than 99.5%; MgCl2 (granular) comes from Fuchen Chemical Reagent Co., Ltd., and the MgCl2 content is not less than 98.0%; Na2SO4 is granular analytical grade, with a content of not less than 99.0%, produced by Tianjin Zhiyuan Co., Ltd.; CaCl2 is granular analytical grade, with a content of not less than 96.0%, produced by Tianjin Zhiyuan Co., Ltd.; potassium chloride is granular analytical grade, with a content of not less than 99.5%, produced by Sinopharm Chemical Reagent Co., Ltd.; NaHCO3 (granular) comes from Tianjin Zhiyuan Co., Ltd., and the NaHCO3 content is not less than 99.5%.
[0021] (5) The alkaline activator is analytically pure anhydrous sodium silicate (Na2SiO3), with a Na2SiO3 content of more than 99% and a modulus of 1.4, produced by Tianjin Zhiyuan Co., Ltd.
[0022] Table 1 Basic physical quantities of slag Table 2 Chemical composition of slag Table 3 Physical properties of three types of sand Table 4 Cumulative sieve residue percentage of three types of sand Formula 1-1 Table 5 Chemical composition of seawater (unit: g / L) Example 1 Alkali slag concrete is prepared using slag, solid sodium silicate, seawater and sea sand.
[0023] (1) Weigh 1828 g of slag, dry it at 60°C for 4 h, cool it to room temperature, and then mix it with 173 g of anhydrous sodium silicate with a modulus of 1.4; (2) The above mixture is placed in a ball mill for ball milling. The slag and alkali are activated by ball milling. The ball mill uses a WZM-15*2 Haoqiang Technology model ball mill, 15L double tank type, and the inner diameter of the ball mill tank is 26cm. The steel ball particle size is 30mm, 20mm and 10mm, and the mass ratio of the three diameter balls is 1:1:1, totaling 15kg. Among them, the ratio of the total mass of the material to the total mass of the three steel balls is 1:7.5 (ball-to-material ratio), that is, the total mass of the slag and anhydrous sodium silicate is 2kg. After sealing, place it on the ball mill for high-speed ball milling (75r / min) for 1h.
[0024] (3) After the ball milling is completed, the powder is poured out and the powder obtained after sieving is the single-component alkali slag cement, which is sealed and stored at a temperature of 20°C-25°C.
[0025] (4) Seawater and sea sand were added in a mass ratio of seawater to single-component alkali-slag cement of 0.43 (water-binder ratio) and a mass ratio of single-component alkali-slag cement to sea sand of 1:2 (binder-sand ratio), and the mixture was stirred using a mortar mixer. The specific process was as follows: 258 g of seawater was added to 600 g of single-component alkali-slag cement, and stirred at a low speed for 30 seconds. Subsequently, 1200 g of sea sand was automatically added for 30 seconds. Then, the mixture was stirred at a high speed for 30 seconds, and a pause of 90 seconds was made in the middle. During the pause, the wall of the pot and the materials precipitated at the bottom were scraped out and stirred evenly. Finally, the mixture was stirred at a high speed for 60 seconds to obtain alkali-slag concrete.
[0026] In order to verify the mechanical properties and drying shrinkage properties of the alkali-slag concrete of this embodiment, an experiment was conducted on the alkali-slag concrete prepared according to the above method.
[0027] The compressive strength and flexural strength tests are carried out in accordance with the "Test Method for Cement Mortar Strength" GB / T 17671-2021. A 40mm×40mm×160mm triple mold is used, and the concrete is molded twice, vibrated 60 times each time, and sealed with plastic wrap for 1 day after smoothing and forming. Nine pieces are made for each group of proportions, three pieces for each. After demolding, the specimens are placed in a standard curing room (temperature 20±2℃, relative humidity above 95%) for curing. After reaching the age (3d, 7d, 28d), the compressive strength and flexural strength are measured using a fully automatic compressive and flexural constant stress testing machine. If the measured value exceeds the average value by ±10%, it will be eliminated and recalculated.
[0028] The test method was formulated with reference to the Standard for Test Methods of Basic Properties of Building Mortar (JGJ / T 70-2009) and the Test Method for Shrinkage of Cement Mortar (JC / T 603-2004). The test used a shrinkage steel mold of 25mm×25mm×280mm, with copper nails reserved at both ends of the steel mold. The slurry was poured in two layers, and the tamping rod was used to tamp 24 times back and forth after each pouring. After tamping, the slurry was smoothed and covered with plastic wrap. To ensure the integrity of the specimen, the specimen was demoulded for 48±2h after adding water. Then the specimen was placed in water at a temperature of (20±2)℃ for curing for 24h. After curing in water, the specimen was taken out and the surface was cleaned. After being placed in a drying shrinkage curing room at a temperature of (20±3)℃ and a humidity of (50±4)% for 4h, the length was measured with a micrometer as the 0d initial length L0 of the specimen. Measure the length L of the specimen at the waiting age of 3d, 7d, 14d, 28d, 42d, 56d, 90d, and 180d t The drying shrinkage St of mortar at different ages is calculated according to the following formula 1-2.
[0029] Example 2 The sea sand was replaced by desalinated sea sand, and the other conditions were the same as those in Example 1 to prepare alkali slag concrete. The specific material physical properties were the same as those in Example 1, and the performance testing steps were the same as those in Example 1.
[0030] Example 3 Alkali slag concrete was prepared by replacing sea sand with river sand and using other conditions as in Example 1. The specific material physical properties were the same as in Example 1, and the performance testing steps were the same as in Example 1.
[0031] Comparative Example 1 The seawater was replaced with deionized water, and the other conditions were the same as those in Example 1 to prepare alkali slag concrete. The specific material physical properties were the same as those in Example 1, and the performance test steps were the same as those in Example 1.
[0032] Comparative Example 2 Alkali slag concrete is prepared using slag, solid sodium silicate, seawater and sea sand.
[0033] (1) Weigh 548 g of slag, dry it at 60 °C for 4 h, cool it to room temperature, and then mix it with 52 g of anhydrous sodium silicate with a modulus of 1.4, that is, the mass of Na2O accounts for 4% of the mass of slag and anhydrous sodium silicate; (2) The obtained mixture was placed in a mortar mixer and stirred for 180 min to obtain a single-component alkali-slag cement prepared by simple mixing.
[0034] (3) Seawater and sea sand were added according to a mass ratio of seawater to single-component alkali-slag cement of 0.43 (water-binder ratio) and a mass ratio of single-component alkali-slag cement to sea sand of 1:2 (binder-sand ratio), and the mixture was stirred using a mortar mixer. The specific process was as follows: 258 g of seawater was added to 600 g of single-component alkali-slag cement, and stirred at a low speed for 30 seconds. Subsequently, 1200 g of sea sand was automatically added for 30 seconds; then, the mixture was stirred at a high speed for 30 seconds, and then paused for 90 seconds. During the pause, the pot wall and the materials precipitated at the bottom were scraped out and stirred evenly; finally, the mixture was stirred at a high speed for 60 seconds to obtain alkali-slag concrete. The performance test steps were the same as those in Example 1.
[0035] Table 6 Mechanical properties of alkali slag concrete in examples and comparative examples Table 7 Drying shrinkage of alkali slag concrete in Examples and Comparative Examples As can be seen from Table 6, the mechanical properties of alkali slag concrete prepared by the mechanochemical method (Examples 1-3) are better than those prepared by the simple mixing method (Comparative Example 2). Under the action of mechanochemical force, the compressive strength and flexural strength of sea sand, desalinated sea sand and river sand all show an increasing trend with increasing age. The 3d compressive strength of sea sand, desalinated sea sand and river sand accounted for 64.5%, 68.8% and 64.4% of the 28d compressive strength, respectively. Therefore, the strength of alkali slag mortar has developed rapidly in the early stage. It can be seen that the early compressive strength of sea sand and desalinated sea sand is very close, and the 28d compressive strength of sea sand relative to desalinated sea sand has increased by 13.16%. There is almost no difference in the flexural strength of sea sand and desalinated sea sand. Compared with river sand, although sea sand will affect the compressive strength of concrete, the compressive strength of Example 1 reached 53.3MPa and the flexural strength was 8.6MPa in 28 days, meeting the basic requirements of application. Compared with the deionized water used in Comparative Example 1, seawater improves the compressive strength of alkali-slag concrete at different ages. The compressive strength of the specimens at 3d, 7d and 28d increased by 6.17%, 1.17% and 18.44% respectively. The reason is that seawater increases the pH value of concrete, and the pH value is very important for the polymerization reaction of alkali-induced materials. Seawater can promote the generation of more CSH gel in alkali-slag materials, resulting in an increase in compressive strength. There is almost no difference in flexural strength.
[0036] As shown in Table 7, the drying shrinkage of alkali slag concrete prepared by the mechanochemical method is smaller than that of the simple mixing method. This may be because the ball milling process will cause the internal pores of the material to change, and the capillary pressure will also change, resulting in a pore size distribution that is beneficial to the drying shrinkage performance. Under the action of mechanochemical force, the drying shrinkage of alkali slag concrete is from low to high in the order of Example 1 < Example 3 < Example 2. That is, the drying shrinkage of alkali slag concrete prepared by sea sand is the lowest, and it is lower than that of alkali slag concrete prepared by river sand. Compared with desalinated sea sand, the drying shrinkage of sea sand at 3d, 56d, and 180d is reduced by 26.84%, 22.82%, and 23.64%, respectively. This is because the chloride ion content of sea sand is higher than that of desalinated sea sand, and the hydration reaction is more intense, so the compressive strength is higher, which is conducive to the reduction of drying shrinkage. Compared with river sand, the drying shrinkage of sea sand at 3d, 56d, and 180d is reduced by 16.22%, 9.78%, and 9.28%, respectively. The reason is that the evaporable water content of sea sand is lower than that of river sand and desalinated sea sand, the CaCO3 crystals in the hydration process are the most, and the microstructure has the least microcracks. Therefore, the preparation of alkali slag concrete with sea sand does not necessarily increase the drying shrinkage. The use of suitable sea sand can alleviate the problem of large drying shrinkage of alkali slag concrete. Within 180 days, the addition of seawater reduces the drying shrinkage of alkali slag concrete. Compared with deionized water, the drying shrinkage of seawater specimens at 28 days, 56 days, and 180 days decreased by 6.60%, 7.80%, and 8.90%, respectively. The reason is that the chloride ions in seawater accelerate the hydration products, so that more hydration products are generated inside the alkali slag mortar prepared by seawater. The generation of hydration products can refine part of the pore structure, hinder the loss of water, and thus reduce shrinkage. In addition, chloride ions themselves have the function of absorbing water and retaining moisture, which also leads to a reduction in drying shrinkage.
[0037] In summary, the alkali slag concrete prepared by mechanochemistry in the present invention achieves the effect of reducing the drying shrinkage rate by using sea sand instead of river sand, which is close to that of ordinary Portland acid cement. This will effectively solve the problem of excessive drying shrinkage rate of alkali slag cementitious materials and provide data support for the further promotion and application of seawater sea sand alkali slag concrete.
[0038] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A method for preparing low drying shrinkage alkali slag seawater sea sand concrete, characterized in that: First, slag and an activator are ball-milled by mechanical chemical force to obtain a powder, namely, single-component alkali slag cement. The slag is S95 grade granulated blast furnace slag, and the activator is anhydrous sodium silicate with an alkali modulus of 1.4, and the mass of Na2O in the anhydrous sodium silicate accounts for 4% of the mass of the slag and the anhydrous sodium silicate. Then, the single-component alkali slag cement is mixed with sea sand and sea water to prepare alkali slag sea water sea sand concrete.
2. The method for preparing low drying shrinkage alkali slag seawater sea sand concrete according to claim 1, characterized in that: The sea sand has a moisture content of ≤6.0%, a mud content of ≤3.0%, a chloride ion content of ≤0.02%, and a shell content of ≤5.0%, calculated by mass percentage.
3. The method for preparing low drying shrinkage alkali slag seawater sea sand concrete according to claim 1, characterized in that: The seawater is prepared according to a concentration ratio of NaCl:MgCl2:Na2SO4:CaCl2:KCl:NaHCO3=24.53:5.2:4.09:1.16:0.695:0.
201.
4. The method for preparing low drying shrinkage alkali slag seawater sea sand concrete according to claim 1, characterized in that: The particle size of the sea sand is less than 5 mm, and the fineness modulus is 2.71, which is medium sand in Zone II.
5. The method for preparing low drying shrinkage alkali slag seawater sea sand concrete according to claim 1, characterized in that: The following steps are involved: (1) After drying and cooling, the slag is mixed with anhydrous sodium silicate with an alkali modulus of 1.4 and ball-milled for 1 h at a speed of 75 r / min and a ball-to-material ratio of 7.5:
1. The powder obtained after ball milling is passed through a sieve plate to obtain a single-component alkali slag cement; (2) Weigh seawater, sea sand and single-component alkali-slag cement according to the proportion, and mix them with a mortar mixer to obtain seawater-sand-alkali-slag concrete.
6. The method for preparing low drying shrinkage alkali slag seawater sea sand concrete according to claim 5, characterized in that: The mass ratio of seawater to single-component alkali-slag cement is 0.43:1; the mass ratio of single-component alkali-slag cement to sea sand is 1:
2.
7. The method for preparing low drying shrinkage alkali slag seawater sea sand concrete according to claim 5, characterized in that: The stirring process is as follows: after adding seawater to the single-component alkali slag cement, stirring at a low speed for 30 seconds, then adding sea sand within 30 seconds, stirring at a high speed for 30 seconds, pausing for 90 seconds to mix the materials, and then continuing to stir at a high speed for 60 seconds.
Citation Information
Patent Citations
Modified geological polymer marine concrete and preparation method
CN109776039A
Alkali-activated slag seawater sea sand concrete and preparation method thereof
CN113816704A
Green low-carbon ultrahigh-performance marine concrete as well as preparation method and application thereof
CN115215617A
Single-component sea sand alkali slag mortar and preparation method thereof
CN116789396A
Seawater-mixed concrete and concrete structure
JP2012126628A
